2002
DOI: 10.1177/002190960203700101
|View full text |Cite
|
Sign up to set email alerts
|

Communicating about AIDS-Changes in Understanding and Coping with Help of Language in Urban Kagera, Tanzania1

Abstract: Faced with the problems of HIV/AIDS, people have to find ways to communicate around them. The aim of this paper is to mirror changes over time in the Kagera people's social cognition regarding HIV/AIDS, using their own language as a tracer of this process. Focus group discussions and personal and group interviews conducted during 1992 to 1995 in urban Bukoba, Kagera, constitute the basis for an analysis of metaphorical expressions in use since 1985. Pronounced uncertainty is later transformed into a deeper und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Many of the organisations and social groups were initiated in the mid 1990s when poverty and the increasing number of deaths due to HIV/AIDS had a great impact on the community. This was also the time when HIV/AIDS started to be seen as a collective responsibility, as indicated by Mutembei, Emmelin, Lugalla and Dahlgren (2002), who observed a change in the local language used when describing AIDS as being "our thing". Formal organisations had started to work more directly with social groups to educate the community about risky health-related behaviour for HIV infection, thereby becoming sources of HIV protective cognitive social capital.…”
Section: Discussionmentioning
confidence: 95%
“…Many of the organisations and social groups were initiated in the mid 1990s when poverty and the increasing number of deaths due to HIV/AIDS had a great impact on the community. This was also the time when HIV/AIDS started to be seen as a collective responsibility, as indicated by Mutembei, Emmelin, Lugalla and Dahlgren (2002), who observed a change in the local language used when describing AIDS as being "our thing". Formal organisations had started to work more directly with social groups to educate the community about risky health-related behaviour for HIV infection, thereby becoming sources of HIV protective cognitive social capital.…”
Section: Discussionmentioning
confidence: 95%
“…Throughout African history, few crises have threatened the very viability of societies, as does the AIDS pandemic. (Villarreal, 2006: 195) HIV/AIDS (Mutembei et al, 2002) both at the company level (Barako and Brown, 2008), community level (Jegede, 2009) and cultural level (Alimi and Bagwasi, 2009). Medical research groups, AIDS/business teams and the health organizations are amongst many key health agents that have ensured that the dissemination of information about HIV/AIDS, and ways to tackle the phenomenon, are known to business leaders who can report these issues to stakeholders in capital markets (UNAIDS, 2000;WEF, 2006;WHO, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the descriptions reported in this study are sharp and witty and may reflect this kind of community coping. Moscovici (in Mutembei, 2002) described two processes by which societies make the unfamiliar familiar. The first is anchoring, which refers to naming the unfamiliar in terms that compare it with what is known.…”
Section: Discussionmentioning
confidence: 99%
“…This could then increase the understanding of the basis of external HIV/AIDS stigma and even of internal stigma. One such a study done in Tanzania was reported by Mutembei, Emmelin, Lugalla, and Dahlgren (2002), who identify three phases in the metaphorical expressions and reactions to the pandemic: first, the stage of uncertainty; then, the phase of growing understanding; and lastly, the current phase of reactions or responses such as coping strategies, warnings, and defeat.…”
mentioning
confidence: 99%